Brachial Plexus Palsy and Shoulder Dystocia: Obstetric Risk Factors Remain Elusive - Ouzounian, Joseph G.; Korst, Lisa M.; Miller, David A.; Lee, Richard H. (American Journal of Perinatology, 2013)
Objective Shoulder dystocia (SD) and brachial plexus palsy (BPP) are complications of childbirth that can result in significant long-term sequelae. The purpose of the present study was to analyze risk factors in cases of SD and BPP.Methods We performed a retrospective study of laboring women who delivered a singleton, term, live-born infant at the Los Angeles County + University of Southern California Medical Center from 1995 to 2004. Multivariable logistic regression models were used to analyze risk factors among SD cases with and without BPP.Results Of the 13,998 deliveries that met inclusion criteria, 221 (1.6%) had SD. Of these, 42 (19.0%) had BPP. After testing for association with multiple potential risk factors, including maternal demographic variables, diabetes, hypertension, prior cesarean delivery, uterine abnormalities, induction of labor, prolonged second stage (adjusted by parity and epidural use), assisted vaginal delivery, and neonatal birth weight, no statistical association of BPP with any specific risk factor was identified.Conclusion In the present study, we were unable to identify any reliable risk factors for BPP among deliveries with or without SD. SD and BPP remain unpredictable complications of childbirth.
Keywords: shoulder dystocia; Erb's palsy; brachial plexus palsy; birth trauma